Analytical and experimental analysis of buck-boost DC-DC converter in photovoltaic (PV) maximum power point tracking application / \c Mohd Nasrul Izzani bin Jamaludin. - Mohd Nasrul Izzani Jamaludin (School of Electrical System Engineering, Universiti Malaysia Perlis, 2017)
The objectives of this project are ; to design and develop a Buck-Boost DC-DC converter for MPP Tracker Application using MATLAB/Simulink® ; to develop a Buck-boost DC-DC converter hardware for MPPT application ; to analyze the performance of PV system with direct load connection and PV system with MPP tracker at different level of irradiance ; to analyze the MPP tracker with Buck-Boost DC-DC converter performance in terms of conversion efficiency and tracking capabilities..